(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the conceptual foundations of radically reforming the pedagogical education system in building the foundation of the Third Renaissance in New Uzbekistan. The differences between the traditional educational format and modern digital-cognitive pedagogy, the competency profile of future teachers, and the practical mechanisms of transforming education are analyzed from a scientific-pedagogical perspective.